AI-driven biomedical and health informatics : Harnessing artificial intelligence for improved healthcare solutions - Usmani, Usman Ahmad; Usmani, Mohammed Umar (Institute of Electrical and Electronics Engineers Inc., 2023)
This paper explores the convergence of Artificial Intelligence (AI) with Biomedical and Health Informatics, focusing on the transformative potential of AI-driven solutions in the healthcare domain. With the growing availability of healthcare data and advancements in AI technologies, there is an increasing emphasis on leveraging AI techniques to enhance medical diag- nosis, treatment, and patient care. This paper highlights recent research and applications that demonstrate the impact of AI in areas such as medical image analysis, disease prediction, drug discovery, and personalized medicine. Additionally, it addresses the challenges and ethical considerations associated with integrating AI into healthcare systems, emphasizing the need for robust and interpretable AI models, data privacy, and trustworthiness. By delving into the opportunities and challenges presented by AI in Biomedical and Health Informatics, this paper aims to inspire further research and collaboration in this promising and critical intersection of disciplines.